The crystal structure of caesalfurfuric acid B, C22H32O4 - Li Xiuyuan; Luo Guoyong; Ye Jianghai; Li Tiantian; Lang Tianqiong (Zeitschrift für Kristallographie - New Crystal Structures)
C22H32O4, monoclinic, P21 (no. 4), a = 12.0894(10) Å, b = 6.4123(5) Å, c = 13.9418(12) Å, β = 112.621(3), V = 997.63(14) Å3, Z = 2, Rgt(F) = 0.0517, wRref(F2) = 0.1312, T = 170 K.